MODEL KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL DALAM PENGELOLAAN SEKOLAH - Ribka Ginting (STKIP Subang, 2026)
Leadership plays a strategic role in determining the success of educational organizations. The differences between transformational and transactional leadership have become an important area of study in understanding leadership effectiveness in schools. This study aims to analyze the conceptual differences between transformational and transactional leadership and to examine their relevance within the context of educational organizations. This research employs a descriptive qualitative approach using a literature review method. Data were collected through an in-depth review of books, scholarly journals, and previous research related to leadership theories. The data were analyzed using content analysis techniques to identify the characteristics, strengths, and implications of both leadership styles. The findings indicate that transformational leadership is more relevant to the educational context because it enhances motivation, commitment, innovation, and collaborative culture. Meanwhile, transactional leadership remains necessary, particularly in administrative management and short-term goal achievement. Therefore, a proportional integration of both approaches is considered an effective strategy to improve performance and the overall quality of educational organizations.